2014
DOI: 10.1161/circulationaha.113.005663
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long-Term Recurrent Vascular Events After Ischemic Stroke at Young Age

Abstract: Background-Data on long-term risk and predictors of recurrent thrombotic events after ischemic stroke at a young age are limited. Methods and Results-We followed 1867 patients with first-ever ischemic stroke who were 18 to 45 years of age (mean age, 36.8±7.1 years; women, 49.0%), as part of the Italian Project on Stroke in Young Adults (IPSYS). Median follow-up was 40 months (25th to 75th percentile, 53). The primary end point was a composite of ischemic stroke, transient ischemic attack, myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 42 publications
8
82
2
1
Order By: Relevance
“…The four-year cumulative risk of recurrent IS was 11.8% in men and 9.8% in women during the last five-year period (2002)(2003)(2004)(2005)(2006), which is slightly higher than that in other previous studies. 10,11,14 In addition, we observed that stroke-free survival improved throughout the study period, but International Journal of Stroke, 11 (1) despite these improvements, almost one in six patients had either died or had a recurrent stroke within four years in the last period. In a report from the population-based Monitoring Trends and Determinants of Cardiovascular Disease Stroke Incidence Registry, a 36% decline in recurrence of stroke was observed in 6700 stroke patients when comparing the periods of 1995-1998 with 2004-2008.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The four-year cumulative risk of recurrent IS was 11.8% in men and 9.8% in women during the last five-year period (2002)(2003)(2004)(2005)(2006), which is slightly higher than that in other previous studies. 10,11,14 In addition, we observed that stroke-free survival improved throughout the study period, but International Journal of Stroke, 11 (1) despite these improvements, almost one in six patients had either died or had a recurrent stroke within four years in the last period. In a report from the population-based Monitoring Trends and Determinants of Cardiovascular Disease Stroke Incidence Registry, a 36% decline in recurrence of stroke was observed in 6700 stroke patients when comparing the periods of 1995-1998 with 2004-2008.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have reported that the risk of a recurrent stroke among younger people within the first year varies from 2 to 4%, decreasing thereafter to less than 3% yearly. [8][9][10][11] Most prior studies on younger adults have been limited by small sample sizes. To the best of our knowledge, no studies have investigated trends and changes in risk over a long period of time in younger patients with ischemic stroke (IS).…”
Section: Introductionmentioning
confidence: 99%
“…4 However, previous studies suggested that in young patients with ischemic stroke, migraine with aura is an independent risk factor of recurrent ischemic stroke and other vascular events. 20 Stroke risk associated with migraine with aura was greater in younger than in older women (45-49 years of age) in the Women's Health Study. 21 Perhaps our participants were too old to display such a relationship between migraine with aura and stroke in both men and women of postmenopausal age.…”
Section: Resultsmentioning
confidence: 97%
“…The primary outcome was a combination of death and major disability (modified Rankin Scale score, [3][4][5][6]. 18 Secondary outcomes were death, major disability, recurrent fatal and nonfatal stroke, and vascular events (eg, vascular deaths, nonfatal stroke, nonfatal myocardial infarction, hospitalized and treated angina, hospitalized and treated congestive heart failure, and hospitalized and treated peripheral arterial disease).…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…3 Anticardiolipin antibodies (aCL) and lupus anticoagulant antibodies were the most frequently studied members and had been associated with an increased risk of recurrent thrombo-occlusive events and death after stroke in some but not in all studies. [4][5][6][7][8] Recently, studies suggest that antibodies directed against phosphatidylserine (antiphosphatidylserine antibodies [aPS]) may be a useful marker for the syndrome. [9][10][11][12] Population-based studies showed an independent association of aPS with ischemic stroke.…”
mentioning
confidence: 99%